1973
DOI: 10.1073/pnas.70.5.1432
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotypic Control by Adenosine 3′:5′-Cyclic Monophosphate: A Model for Growth Control in Animal Cells

Abstract: The effects of serum deprivation on several general cellular biochemical processes ("pleiotypic response") related to the growth of normal fibroblasts can be mimicked by treatment of these cells with prostaglandin El in the presence of serum. N8,02'-Dibutyryl adenosine 3': 5'-cyclic monophosphate and theophylline inhibit the membrane transport processes without much effect on other pleiotypic reactions such as overall protein and RNA synthesis and protein degradation. The amount of intracellular cyclic AMP inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
66
0
2

Year Published

1974
1974
1988
1988

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(71 citation statements)
references
References 30 publications
3
66
0
2
Order By: Relevance
“…In studies with rat mammary gland explants in culture [2] cyclic AMP inhibited the increase of enzyme activities normally associated with lactogenesis, in particular the activities of those enzymes involved in lipogenesis, and also markedly depressed the synthesis of DNA, RNA and fatty acids. This analogy with the pleiotypic response observed for other cells grown in culture [3], and the reversal by cyclic GMP of the pleiotypic inhibition of 3T3 cells treated with dibutyryl cyclic AMP [4] , led us to investigate the simultaneous fluctuations of both cyclic nucleotides throughout the lactation cycle. differentiation of the mammary gland during pregnancy, its response to hormones and the promotion of specific cell programmes for the synthesis of the characteristic components of milk may all be mediated by modification of the ratio between the two nucleotides.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…In studies with rat mammary gland explants in culture [2] cyclic AMP inhibited the increase of enzyme activities normally associated with lactogenesis, in particular the activities of those enzymes involved in lipogenesis, and also markedly depressed the synthesis of DNA, RNA and fatty acids. This analogy with the pleiotypic response observed for other cells grown in culture [3], and the reversal by cyclic GMP of the pleiotypic inhibition of 3T3 cells treated with dibutyryl cyclic AMP [4] , led us to investigate the simultaneous fluctuations of both cyclic nucleotides throughout the lactation cycle. differentiation of the mammary gland during pregnancy, its response to hormones and the promotion of specific cell programmes for the synthesis of the characteristic components of milk may all be mediated by modification of the ratio between the two nucleotides.…”
Section: Introductionmentioning
confidence: 72%
“…Some of these activities may be highly relevant to the mammary gland a) the role of cyclic AMP as promoter of differentiation could be of special significance to the development of the gland during pregnancy, a stage at which the level of this nucleotide is high; b) the rise of cyclic GMP after the onset of lactation may explain the wave of mitosis which follows shortly after parturition in the rat [23], a process which is also significant (in addition to increasing the number of secretory cells present) in that it may, as suggested by Stockdale and Topper [24] , make these cells specially susceptible to environmental factors capable of modifying the metabolic pattern; c) the complex endocrine control of the mammary gland and the tissue response to hormones may be expressed through the dualistic system of opposing cyclic AMP and cyclic GMP levels which could, as has already been shown for other cells grown in culture [3,4] , also modulate the pleiotypic control of mammary cells [2] .…”
Section: Resultsmentioning
confidence: 99%
“…It was suggested that the changes of cyclic nucleotides regulate the cell cycle and more generally that cyclic nucleotides are involved in the "pleiotypic" control of cell growth (5,6 The aim of the present work was to analyze the evolution pattern of adenylate cyclase during the cell cycle in neuroblastoma cells and the evolution patterns of the responses to three different regulatory agents: adenosine, dopamine, and prostaglandin (PG) El. The latter seems to be a candidate for intracellular regulation because several cell lines, including neuroblastoma, are able to synthesize prostaglandins (7).…”
mentioning
confidence: 99%
“…We are tempted to suggest that this phenomenon might be related to a different availability of free and more active polycations inside the cell. However, considering the inverse correlation between growth rate and cyclic AMP concentrations (Otten et al, 1972;Kram et al, 1973;Bombik & Burger, 1973), the opposite effects elicited by low or high exogenous polyamine concentrations are consistent with their observed ability to act as promoters (Ham, 1964;Clo et al, 1976) or inhibitors (Halevy et al, 1962;Gahl et al, 1976) of cell growth, respectively.…”
Section: Discussionmentioning
confidence: 93%